Oral N-Acetyl cysteine lowered IL 6 level among stage V chronic kidney disease patients on Continuous Ambulatory Peritoneal Dialysis (CAPD) - Evi Nurhayatun (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background. IL 6  level is increased in stage V CKD patients on CAPD. N-Acetyl Cysteine is a compound containing thiol with antioxidant and anti-inflammatory effects.Objective. To examine the effect of oral NAC on IL 6 level in stage V CKD patients on CAPD.Method. An experimental research with Randomized Double Blind Control Trial,  involving 30 CKD patients on CAPD in Dr Moewardi Hospital. They were divided into control group/placebo (15 patients) and oral NAS treatment group (15 patients). IL 6 level was measured before and after 8 weeks of treatment.Result. Level of IL 6  before and after treatment in control group were (8.13 +7.62  vs 11.16 + 8.32 , p= 0,001), significantly (p<0,001). Level of IL 6 before and after treatment in treatment group were (9.72 + 7.29 vs 6.09 + 3.82, p = 0,002); lowered significantly (p<0,05).Conclusion. Oral NAC lowered the level of IL 6 in stage V CKD patients on CAPD.